Math, asked by sanand09011, 4 months ago

(-3+ √5)(-3 - √5) simplify​

Answers

Answered by maryvarsha2413
1

Answer:

4

Step-by-step explanation:

(a+b)*(a-b)=a^{2}-b^{2}

(-3+\sqrt{5})(-3-\sqrt{5})=(-3)^{2}-(\sqrt{5}) ^{2}

                                =9-5

                                =4

Answered by saruot7
1

Answer:

4

Step-by-step explanation:

( - 3 +  \sqrt{5)} ( - 3 - \sqrt{5)}

 = ( { - 3})^{2}  - ( \sqrt{5)}^{2}

using \: identity

(a  + b)(a - b) =  {a}^{2}  -  {b}^{2}

 = 9 - 5

 = 4

Similar questions